Engineered exciton diffusion length enhances device efficiency in small molecule photovoltaics. Issue 20 (8th May 2018) - Sajjad, Muhammad T.; Blaszczyk, Oskar; Jagadamma, Lethy Krishnan; Roland, Thomas J.; Chowdhury, Mithun; Ruseckas, Arvydas; Samuel, Ifor D. W.
Abstract : A post processing method of solvent vapor annealing (SVA) enhances the diffusion length ( L D ) and domain size in small molecule organic semiconductors which leads to an enhancement in device performance in bulk heterojunction organic photovoltaics. Abstract : In organic photovoltaic blends, there is a trade-off between exciton harvesting and charge extraction because of the short exciton diffusion length. Developing a way of increasing exciton diffusion length would overcome this trade-off by enabling efficient light harvesting from large domains. In this work, we engineered (enhanced) both exciton diffusion length and domain size using solvent vapour annealing (SVA). We show that SVA can give a three-fold enhancement in exciton diffusion coefficient ( D ) and nearly a doubling of exciton diffusion length. It also increases the domain size, leading to enhancement of charge extraction efficiency from 63 to 89%. Usually larger domains would reduce exciton harvesting but this is overcome by the large increase in exciton diffusion, leading to a 20% enhancement in device efficiency.